2010
DOI: 10.7326/0003-4819-153-2-201007200-00262
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Osteoporosis: An Update for the U.S. Preventive Services Task Force

Abstract: Agency for Healthcare Research and Quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(150 citation statements)
references
References 129 publications
3
138
0
9
Order By: Relevance
“…4 The United States Preventive Services Task Force (USPSTF) recommends dual-energy x-ray absorptiometry (DXA) screening for women aged 65 and older and for younger women who have a fracture risk greater than or equal to the risk of a 65 year old white female with no additional risk factors. 5 The National Osteoporosis Foundation has issued similar recommendations. 6 The extent to which clinicians adhere to USPSTF recommendations is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…4 The United States Preventive Services Task Force (USPSTF) recommends dual-energy x-ray absorptiometry (DXA) screening for women aged 65 and older and for younger women who have a fracture risk greater than or equal to the risk of a 65 year old white female with no additional risk factors. 5 The National Osteoporosis Foundation has issued similar recommendations. 6 The extent to which clinicians adhere to USPSTF recommendations is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A Quantitative ultrasonography study indicated that no significant difference of BMD was found in an eight-year interval in a cohort consisting of healthy, older, postmenopausal women [105]. The revised and expanded recommendations in 2010 by the U.S. Preventive Services Task Force (USPSTF) underscore the need for more screening of the bone density [106]. The time interval of monitoring bone mineral density relies on both the precision error of the method used and the rate of bone loss for the population studied.…”
Section: Follow-up Time Using the Qctmentioning
confidence: 99%
“…Since the menopause is a readily recognizable event, a number of analyses have been carried out where it has been used as a time when to start screening women for osteoporosis using BMD [15][16][17]. The cost of screening itself is not the dominant factor, because most treatments are more expensive (though this may vary between countries) and may have side effects.…”
Section: Screening At the Menopausementioning
confidence: 99%